Absenteeism: a retrospective cross–sectional study among employees of the Keratsini Municipality for the year 2022 - Sarros, Georgios; Menti Ariadni; Katrachouras Ioannis; Stergiakouli Vasiliki; Makrynos George; Rapisarda Venarando; Georgios Dounias (International Journal of Occupational Safety and Health, 2026)
Introduction: Absenteeism is a multifactorial phenomenon. The study aimed to analyze specific indicators (Absenteeism rate, Frequency of sickness absence, Cumulative incidence, Duration of absence, Length of sickness absence, Bradford Score) among municipal employees and to compare them across certain variables (gender, position, age, seniority). Methods: In this retrospective cross-sectional study, the sample was the employees of the Municipality of Keratsini for year 2022. Data were collected through the individual employees’ sick leave file, processed with Microsoft Excel and statistically analyzed with Stata (chi-square tests). A comparison of the results between two previous studies with the same sample followed. Results: Females (n=179/45.8%) received statistically sick leave more frequently (females with at least one sick leave: n=148/82.7%, males with at least one sick leave: n=128/60.4%) (p<0.005) and employees with 20-29 years of service (n=117/29.9%) received significantly more likely to take sick leave (employees with 20-29 years of service with at least one sick leave: n=89/76.1%) (p=0.04). Regarding the 3 studies’ comparison, there was an increase in the number of absentees (2001: n=155/55%, 2007: n=134/40%, 2022: n=276/70.5% (p<0.001) and in the granting of sick leave with a medical certificate (2001: n=219/45.7% 2007: n=133/39%, 2022: n=252/30%) (p<0.001) and a health board (2001: n=110/23% 2007: n=102/29.9%, 2022: n=304/36.3%) (p<0.001). Conclusion: Absenteeism indicators can reveal groups or individuals with an increased propensity to receive sick leave. Some of the study’s results aligned to international literature (category of female employees, category of cleaning employees). Longitudinal comparison revealed an increase in absenteeism that could be justified by a number of factors (increased age, COVID-19 pandemic, periods of economic or health crisis). A number of countermeasures are suggested (close monitoring, return-to-work interviews, vaccination, ensuring personal hygiene in the workplace, upgrade of the role of occupational physicians).